Features of group psychological work with children who have received traumatic experience - Bondaruk , Yuliia (Psychological Prospects Journal, 2020)
Purpose. The article considers the issues of providing psychological assistance to traumatized children who suffered as a result of the military conflict and found themselves in difficult life circumstances. The purpose of the article is to characterize the main factors that affect the effectiveness of group psychological work with injured children in an educational institution. The research methods are the analysis and generalization of theoretical sources of domestic and foreign scientists on the provision of psychological assistance to affected children who have received traumatic experiences.The results of the analysis of theoretical sources allow identifying and characterizing the main psychological approaches in dealing with trauma in children, which are most often presented within the game approach in its various modifications: client-centered orientation, structural game therapy or other types.Analysis of research suggests that the main goals in helping children are to respond to traumatic experiences, stabilize emotional state and restore social interaction between children and the main methods of work of a psychologist are those based on child-centered play therapy. In the case when a child experiences a certain event not once, but finds himself in new (or difficult) life circumstances, the task of psychological help will not be emotional response, but adaptation, and in this case a more effective approach based on social learning theory. Conclusions. The main factors influencing the effectiveness of group work with children are the construction and organization of play in accordance with the stages of psychotrauma, selection and possession of appropriate methods and techniques taking into account the age and individual characteristics of children, as well as group processes. To these factors should be added the experience of working with traumatic experiences in children, professionalism and personal qualities of the group leader.
Keywords: psychological trauma; group process; game therapy; interaction; children; methods; response